Identity Politics in Muslim Societies and the Ethical Limits of Religious Mobilization - Nabilah Batu bara; Nazwatul Jannah Harahap; Rizky Puji Gunawan Nasution; Yanuardin; Ilham Hasan (Young Journal of Social Sciences and Humanities, 2026)
Identity politics is a persistent feature of contemporary democratic life, yet its operation in Muslim-majority societies is analytically ambivalent. Religious identity can provide a legitimate basis for recognition, solidarity, moral advocacy, and political participation, but it can also be converted into an exclusionary boundary that intensifies polarization, intolerance, and intergroup conflict. This article examines the drivers, forms, consequences, and ethical limits of religious identity politics, with Indonesia as the principal empirical context. It employs a qualitative literature-review design. The review identifies five interconnected drivers: social cleavage, elite political mobilization, economic inequality, perceived discrimination, and digital-media amplification. These drivers are expressed through religiously framed campaigning, symbolic political representation, in-group/out-group narratives, group fanaticism, and digitally mediated mobilization. The analysis shows that the democratic effects of identity politics depend less on the presence of religious identity than on the mode of mobilization. Identity may strengthen representation and civic participation when it articulates legitimate grievances without denying equal citizenship; it becomes democratically corrosive when religious belonging is instrumentalized to delegitimize opponents or monopolize moral authority. Drawing on Islamic principles of justice, brotherhood, unity, moderation, and recognition of diversity, the article proposes a normative continuum from identity recognition to exclusionary identity mobilization.